1+0.6(q-4)=0.49(q+1)

Simple and best practice solution for 1+0.6(q-4)=0.49(q+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+0.6(q-4)=0.49(q+1) equation:


Simplifying
1 + 0.6(q + -4) = 0.49(q + 1)

Reorder the terms:
1 + 0.6(-4 + q) = 0.49(q + 1)
1 + (-4 * 0.6 + q * 0.6) = 0.49(q + 1)
1 + (-2.4 + 0.6q) = 0.49(q + 1)

Combine like terms: 1 + -2.4 = -1.4
-1.4 + 0.6q = 0.49(q + 1)

Reorder the terms:
-1.4 + 0.6q = 0.49(1 + q)
-1.4 + 0.6q = (1 * 0.49 + q * 0.49)
-1.4 + 0.6q = (0.49 + 0.49q)

Solving
-1.4 + 0.6q = 0.49 + 0.49q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-0.49q' to each side of the equation.
-1.4 + 0.6q + -0.49q = 0.49 + 0.49q + -0.49q

Combine like terms: 0.6q + -0.49q = 0.11q
-1.4 + 0.11q = 0.49 + 0.49q + -0.49q

Combine like terms: 0.49q + -0.49q = 0.00
-1.4 + 0.11q = 0.49 + 0.00
-1.4 + 0.11q = 0.49

Add '1.4' to each side of the equation.
-1.4 + 1.4 + 0.11q = 0.49 + 1.4

Combine like terms: -1.4 + 1.4 = 0.0
0.0 + 0.11q = 0.49 + 1.4
0.11q = 0.49 + 1.4

Combine like terms: 0.49 + 1.4 = 1.89
0.11q = 1.89

Divide each side by '0.11'.
q = 17.18181818

Simplifying
q = 17.18181818

See similar equations:

| 40-8x=-5(-6+2x) | | -13+y/9=-24 | | 4x^2+17x+24=0 | | g/8=-3/4 | | 19a+12b+a-2b= | | 5x-2(4+3x)=11 | | 150m-125m+38000=41000-175 | | 6+k/4=14 | | 19=z-1.1 | | 3x+19=-36 | | t+(-4)=10 | | 2(-6v-1)=33-5v | | a+1(1/4)=2(7/10) | | 2y=3x-18 | | x^3-5x^2+4x+10=0 | | -8n+11=-7n-18 | | -28x^5-4x^4= | | -8x-2=-2(4x+1) | | r+25-5= | | x-0.7=10 | | 3(x+2)=x-15 | | -1+(-8)= | | 2=y/5-8 | | 50-30x=75 | | -2y-12=4y+24 | | -7(c+9)=9(c-5)-14c | | 10/3+8= | | k-31=5(1-7k) | | 4n+3=n-17 | | y^2=12y-35 | | 5y-1=2y+5 | | ABD=180(5y+1) |

Equations solver categories